Semiotika Dakwah Digital dalam Meme Ajakan Salat Jumat - Sunaryanto Sunaryanto; Ahmad Rofi Syamsuri (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2022)
The phenomenon of da'wah in the digital era is now increasingly diverse. The emergence of memes into ideas and behaviors that act as persuasive messages. Memes are used to package digital da'wah messages including invitations to carry out Friday prayers. The purpose of this study is to analyze the meaning of digital da'wah memes inviting Friday prayers on the internet. This article uses qualitative research with semiotic analysis which is part of the textual analysis of the mass media. The findings in this study are digital da'wah signs in memes inviting Friday prayers, namely hats, white koko shirts, mics, headscarves, Al-Qur'an and others. The digital da'wah markers in the meme are Rhoma Irama, Joko Widodo, Prabowo Subianto, and beautiful women. Digital da'wah memes that are interpreted are piety, creed, politicization of religion, and political campaigns. The denotation meaning of digital da'wah in the meme is a good leader, even though he is busy, does not leave the obligation of Friday prayers. Friday prayers should be understood by Muslim men as compared to Friday night worship (i.e. husband and wife relations). The connotative meaning is that Friday prayers are understood as an attempt to gain political mass. Friday prayers are considered as a way to be handsome in this world only and not handsome in the hereafter. Digital da'wah in invitations to Friday prayers can be interpreted in three contexts, namely Islam, culture and politics.